1, 25(OH)2D3 blocks IFNβ production through regulating STING in epithelial layer of oral lichen planus. Issue 13 (29th May 2022) - Ge, Xuejun; Wang, Yaxian; Xie, Hanting; Li, Ran; Zhang, Fang; Zhao, Bin; Du, Jie
Abstract: Stimulator of interferon genes (STING) is reported to exert vital functions in inflammatory responses and autoimmune diseases. Nevertheless, the status and roles of STING in oral lichen planus (OLP) remain elusive. Here, we state that STING and its downstream cytokine interferon‐β (IFNβ) expression is boosted in the oral keratinocytes from patients suffering OLP in comparison with those from healthy participants. Mechanistically, transcription factor GATA‐binding protein 1 (GATA1) which is highly increased in diseased samples specifically interacts with its element in the promoter of STING to enhance STING transcripts. 1, 25(OH)2 D3, the active form of vitamin D, is capable of restricting STING and IFNβ increases in oral keratinocyte models resembling OLP in vitro. Moreover, there is a negative correlation between vitamin D receptor (VDR) and STING or IFNβ in human samples. Using plasmids and small interfering RNA transfection technologies, we find 1, 25(OH)2 D3 regulates STING and IFNβ through a mechanism controlled by the hypoxia‐inducible factor‐1α (HIF‐1α)‐GATA1 axis. Collectively, our findings unveil that 1, 25(OH)2 D3 lowers STING and IFNβ overexpression in the context of OLP.